2014
DOI: 10.1002/jctb.4406
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of olive oil mill wastewater by a pulsed high‐voltage discharge process; process optimization and combination with Fe+2 and H2O2

Abstract: BACKGROUND: Olive oil mill wastewaters (OOMW) have caused major environmental problems because of the high organic load, high total suspended solids, high inert chemical oxygen demand (COD), low pH, a characteristic odour, its dark colour and toxicity to plants. A pulsed high-voltage discharge (PHVD) process was developed as a novel alternative to advanced oxidation processes for effective treatment of OOMW. RESULTS:The ability of a PHVD process, after acid cracking, to treat OOMW, was investigated. For a PHVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Ibrahimoglu and Yilmazoglu [8] reported a 99.3% reduction of COD, and color reduced by 99.2% in OMWW treated with DC arc plasma. Pulsed high-voltage discharge plasma resulted in 72% COD and 74% phenol degradations with the addition of H 2 O 2 , and 74% COD and 79% phenol degradation with the addition of ferrous ions from OMWW [9].…”
Section: Cod Removalmentioning
confidence: 99%
See 3 more Smart Citations
“…Ibrahimoglu and Yilmazoglu [8] reported a 99.3% reduction of COD, and color reduced by 99.2% in OMWW treated with DC arc plasma. Pulsed high-voltage discharge plasma resulted in 72% COD and 74% phenol degradations with the addition of H 2 O 2 , and 74% COD and 79% phenol degradation with the addition of ferrous ions from OMWW [9].…”
Section: Cod Removalmentioning
confidence: 99%
“…A promising method for OMWW degradation is plasma technology, mainly because of environmental compatibility and high removal efficiency. However, there is little information on the use of plasma in OMWW treatment [8,9]. Ibrahimoglu and Yilmazoglu [8] treated OMWW with the DC arc plasma method and reported that the rates of COD (chemical oxygen demand) and BOD (biological oxygen demand) of OMWW decreased by 94.42% and 95.37%, respectively, with a color removal rate of 99.2%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations